2022
DOI: 10.1093/eurheartj/ehac544.946
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abstinence vs. persistent alcohol consumption in alcoholic cardiomyopathy: impact on long-term prognosis

Abstract: Background Alcoholic Cardiomyopathy (ACM) remains a prevalent form of toxic-induced heart damage. Whether ACM prognosis depends on the persistence of alcohol consumption is a matter of debate. Purpose We sought to determine predictors of adverse events during long-term follow-up and left ventricular ejection fraction (LVEF) changes between abstainers and non-abstainers. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[ 45 ] However, a more recent study from 2022 has shown that abstinence led to statistically significant LVEF improvement compared with moderate drinking. [ 46 ] Despite this, complete alcohol abstinence has remained the recommendation because it is considered that maintaining mild–moderate alcohol intake is difficult, with a high risk of relapsing to heavy alcohol use. To encourage and maintain abstinence, a combination approach using pharmacological and psychological therapies should be employed.…”
Section: Alcoholic Dilated Cardiomyopathymentioning
confidence: 99%
“…[ 45 ] However, a more recent study from 2022 has shown that abstinence led to statistically significant LVEF improvement compared with moderate drinking. [ 46 ] Despite this, complete alcohol abstinence has remained the recommendation because it is considered that maintaining mild–moderate alcohol intake is difficult, with a high risk of relapsing to heavy alcohol use. To encourage and maintain abstinence, a combination approach using pharmacological and psychological therapies should be employed.…”
Section: Alcoholic Dilated Cardiomyopathymentioning
confidence: 99%